The Great Recession: US dynamics and spillovers to the world economy - Bagliano, Fabio C.; Morana, Claudio (Journal of Banking & Finance, 2012)
This paper provides an empirical investigation of both the within-US and international channels of transmission of macroeconomic and financial shocks by means of a 50-country macroeconometric model (estimated over the 1980–2009 period), including measures of excess liquidity and financial fragility, specifically designed in order to evaluate the relevance of the boom-bust credit cycle view put forward as an interpretation of the recent “Great Recession” episode. We find that such a view is consistent with the empirical evidence. Moreover, concerning the real effects of financial shocks within the US, we detect stronger evidence of an asset prices channel, rather than a liquidity channel. Concerning the spillovers to the world economy, we find that while financial disturbances are transmitted to foreign countries through US house and stock price dynamics, as well as excess liquidity creation, the trade channel is the key trasmission mechanism of real shocks.